Co-explosivity versus leading effects: Evidence from crude oil and agricultural commodities - Ghassen, El Montasser (2023)
Unlike previous studies investigating the interdependence and co-movements between different commodity prices, this paper examined the co-explosivity versus leading effects between the Brent oil prices and agricultural commodity prices. Empirically, we first date-stamped bubbles in the Brent and a set of agricultural commodities. Second, we examined possible existence of co-explosivity between these commodities' prices. Finally, by using predictive quantile regressions, we examined the leading effects of the crude oil market on agricultural commodity markets and vice versa. The results provide strong evidence for the presence of bubbles in the Brent oil price and the eight selected agricultural commodities’ prices. In particular, we found that the year 2008 had the largest number of Brent-related bubbles, as well as a large proportion of bubbles in the studied agricultural commodities. However, although we found no evidence of co-explosivity between the different commodities, the results highlight strong evidence of the presence of leading effects from Brent oil prices to agricultural commodities for different lags. The reverse leading effect was found for only the corn and soybean commodities. The important implications for investors and market participants were presented and discussed.